The early work of Valentin Serov in the context of European painting: the example of Olga Trubnikova portrait of 1886 - Malycheva, Tanja (Actual Problems of Theory and History of Art, 2012)
The portrait of Olga Trubnikova created in 1886 is one of Serov’s fi rst pictures showing the influence of the works by European artists and also his autonomy in style and content. In this context the article discusses works by Rembrandt, Vermeer, Israëls, Liebermann, and others that Serov might have seen during his trip to Europe in summer 1885. Besides, it briefly defines the role the cities he visited played in Europe’s artistic and cultural development at the end of the 19th century.
Keywords: Valentin Serov; Olga Trubnikova; portrait; iconography; Hague School; Karl Koepping; Rembrandt Harmenszoon van Rijn; Jan Vermeer; Max Liebermann; Jozef Israëls